2019
DOI: 10.1371/journal.pone.0223519
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq analysis reveals an essential role of tyrosine metabolism pathway in response to root-rot infection in Gerbera hybrida

Abstract: Gerbera hybrida is one of the top five cut flowers across the world, it is host for the root rot causing parasite called Phytophthora cryptogea. In this study, plantlets of healthy and root-rot pathogen-infected G. hybrida were used as plant materials for transcriptome analyis using high-throughput Illumina sequencing technique. A total 108,135 unigenes were generated with an average length of 727 nt and N50 equal to 1274 nt out of which 611 genes were identified as DEGs by DESeq analyses. Among DEGs, 228 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 76 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…As for the other metabolites discussed, a role of these alkaloids in the protection against P. cinnamomi can be suggested. Our results agree with those of Munir et al [ 80 ] on Gerbera hybrida , pointing out the role of the tyrosine metabolic pathway in response to the Phytophthora cryptogea root-rot-causing agent.…”
Section: Discussionsupporting
confidence: 93%
“…As for the other metabolites discussed, a role of these alkaloids in the protection against P. cinnamomi can be suggested. Our results agree with those of Munir et al [ 80 ] on Gerbera hybrida , pointing out the role of the tyrosine metabolic pathway in response to the Phytophthora cryptogea root-rot-causing agent.…”
Section: Discussionsupporting
confidence: 93%
“…SIN_1023218 encodes alanine glyoxylate aminotransferase 2, which is involved in the transfer and catalysis of amino acids (Liepman and Olsen, 2003). SIN_1023221 and SIN_1023287 encode 2-oxoglutarate-dependent dioxygenase and beta-glucosidase, respectively, which are essential enzymes in flavonoid and phenylpropanoid biosynthesis (Farrow and Facchini, 2014;Munir et al, 2019). These are all potential regulatory pathways related to seed coat pigment accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The first step in the biosynthesis of ubiquinone and other terpenoid quinones is the generation of 4-coumaric acid from trans-cinnamic acid ester catalyzed by trans-cinnamic acid 4-monooxygenase, which is hydroxylated by 4-coumaric acid-coenzyme A ligase (4Cl) to generate β-coumaric acid-coenzyme A, which is involved in the flavonoid biosynthetic pathway [ 56 ]. Meanwhile, 4Cl plays an important role in plant biosynthesis and affects the accumulation of phenylpropane in plants [ 57 ]. In this study, some DEPs were found to be enriched in a large number of secondary metabolism-related pathways after drought stress, including flavonoid biosynthesis, terpene skeleton biosynthesis, carotenoid biosynthesis, sesquiterpene and triterpene biosynthesis, and phenol propane biosynthesis ( Table S 3 ).…”
Section: Discussionmentioning
confidence: 99%